Method for synergistic detoxification and all-component resource utilization of multi-source carbon-containing solid waste

By controlling the particle size of multi-source carbon-containing solid waste, mixing activation machinery and co-treating high-value ice crystals and high-performance gelling materials in the existing technology, the problems of large land occupation, high pollution risk and insufficient resource utilization of multi-source carbon-containing solid waste treatment are solved, and the efficient, economical and environmentally friendly effects of coordinated detoxification and full-component resource utilization are achieved.

CN119771900AActive Publication Date: 2025-04-08GUIZHOU NORMAL UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411971735.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-08
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

When dealing with multi-source carbon-containing solid waste, the existing technology has problems such as large land occupation, high pollution risk, and insufficient resource utilization, making it difficult to achieve coordinated detoxification and full-component resource utilization.

Method used

By controlling and drying the multi-source carbon-containing solid waste, it is divided into high-fluorine materials and solidified materials, and is mixed with activation machinery, and then co-treated under a high temperature environment to generate tailings and fluorine-containing flue gas. Through inducer and pH regulation, fluorine-containing flue gas is converted into high-value crystalline crystals, and the tailings are mixed with aluminosilicate solid waste to prepare high-performance gelling materials.

Benefits of technology

The coordinated detoxification of multi-source carbon-containing solid waste and full-component resource utilization are achieved. The entire process is closed-loop treatment, no secondary pollution risk, and no additional chemicals are required, which is cheap in disposal. The carbon components, fluoride components and other inorganic salt components in multi-source carbon-containing solid waste can be used for fuels, high-value ice crystal products and high-performance gelling materials respectively, and have significant economic and environmental benefits.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention belongs to the technical field of solid waste resource utilization, and particularly relates to a multi-source carbon-containing solid waste synergistic detoxification and all-component resource utilization method which comprises the following steps: firstly, performing granularity control and drying treatment on multi-source carbon-containing solid waste to obtain a high-fluorine material and a solidified material; adding the high-fluorine material and the curing material according to a ratio, activating and mixing to obtain a mixed material, placing the mixed material in high-temperature treatment equipment, co-treating in an air environment to obtain tailings and fluorine-containing flue gas, introducing the fluorine-containing flue gas into a collecting solution, treating to obtain cryolite and filtrate, mixing the tailings and aluminosilicate solid waste, and recycling the mixed material to obtain the product. And treating to obtain the cementing material. According to the method, collaborative detoxification and all-component resource utilization of the multi-source carbon-containing solid waste are achieved, the whole collaborative treatment process is closed-loop treatment, and the risk of secondary pollution is avoided; the carbon component, the fluoride component and other inorganic salt components can be respectively suitable for fuels, high-value cryolite products and high-performance cementing materials, and have remarkable economic and environmental benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of comprehensive utilization of solid waste resources, and specifically relates to a method for the coordinated detoxification of multi-source carbon-containing solid waste and resource utilization of all components. Background Art

[0002] At present, the wet recycling of retired lithium-ion batteries, the production of primary aluminum, the thermal decomposition of sludge, and coal mining processes all produce a large amount of solid waste rich in carbonaceous materials and environmentally unfriendly substances, which have the dual attributes of environmental pollution risks and resource utilization. Therefore, achieving the coordinated detoxification and full component resource utilization of the above-mentioned multi-source carbon-containing solid waste is of great significance to the national ecological civilization construction and resource security major strategy. The disposal methods for the above-mentioned carbon-containing solid waste at home and abroad are mainly divided into the following categories:

[0003] The first method is landfill disposal, which involves reducing the carbonaceous solid waste to a finer particle size, compressing it, and then landfilling it in an impermeable site. Drainage pipes are laid at the bottom of the site to drain the leachate for detoxification, thus achieving safe disposal of the carbonaceous solid waste. However, this method requires significant land, is prone to leaks and contaminate the surrounding environment, and leaves a significant amount of high-quality carbonaceous materials and high-value fluorides unutilized.

[0004] The second method is flotation treatment, which mainly utilizes the wettability difference between carbon components and non-carbon components in carbon-containing solid waste. Through the interaction between surfactants and carbon components, carbon particles in the slurry come into contact and collide with a large number of bubbles generated by the surfactants, and eventually adhere to the surface of the bubbles and float out, thereby achieving effective recovery of carbon components in carbon-containing solid waste. Its disadvantages are that the recovered carbonaceous materials have a relatively low fixed carbon content, lacking large-scale resource utilization channels, and some water-soluble toxic substances enter the flotation solution, posing a serious risk of secondary pollution.

[0005] The third method is direct resource recovery. This method primarily utilizes the high energy density of the carbon component in carbon-containing solid waste. This method, crushed to a certain particle size, directly feeds the carbon-containing solid waste into the blast furnace ironmaking or cement production process. The carbon component burns to generate a large amount of heat, while the non-carbon components enter the slag or cement matrix, thereby achieving detoxification and resource utilization of the carbon-containing solid waste. However, its disadvantages are that the high sulfur content produces a large amount of polluting gases, and high-value fluorides are converted into solid residues, posing a significant risk of secondary pollution.

[0006] The fourth method involves valuable component recovery. This approach primarily leverages the phase transition characteristics of non-carbon components in carbonaceous solid waste. High-temperature treatment, wet leaching, or molten salt roasting are then used to construct single- or multi-stage recovery systems. This system then recycles the refined carbonaceous solid waste, achieving a cascade recovery of carbon components and various non-carbon valuable components. However, its disadvantages are that high-temperature treatment involves significant energy consumption and carbon emissions, wet leaching involves highly corrosive agents such as acids and alkalis, and molten salt roasting is complex and expensive. Summary of the Invention

[0007] In order to solve the problems existing in the prior art, the main purpose of the present invention is to propose a method for the coordinated detoxification and resource utilization of multi-source carbon-containing solid waste and all components, so as to realize the coordinated and safe disposal of toxic substances in multi-source carbon-containing solid waste, the dilution of sulfur content and the optimization of the combustion process. The waste gas and waste residue are used for the synthesis of high-value fluorides and the preparation of cementitious materials respectively, which has the characteristics of high efficiency, simple process and significant economic and environmental benefits.

[0008] To solve the above technical problems, according to one aspect of the present invention, the present invention provides the following technical solutions:

[0009] A method for collaborative detoxification and resource utilization of multi-source carbon-containing solid wastes, comprising the following steps:

[0010] S1. Control the particle size and dry the carbon-containing solid waste from multiple sources in sequence to separate it into high-fluorine materials and solidified materials;

[0011] S2. Add the high-fluorine material and the solidified material in proportion and activate them mechanically to obtain a mixed material;

[0012] S3, co-processing the mixed material at high temperature in an air environment to obtain tailings and fluorine-containing flue gas;

[0013] S4, passing the fluorine-containing flue gas into an aqueous solution for collection, and sequentially performing the steps of adding an inducer, adjusting the pH, and performing solid-liquid separation to obtain cryolite and a filtrate;

[0014] S5. Mix the tailings and aluminosilicate solid waste, add an alkali activator, and sequentially perform wet mixing, alkali activation, gasification, curing, and autoclaving to obtain a cementitious material.

[0015] The multi-source carbon-containing solid waste in the present invention refers to solid waste with carbon as the main component from different industries, mainly coal gangue from the coal industry, waste cathode carbon blocks from the aluminum electrolysis industry, pyrolysis residues from oily sludge from the petroleum industry, and wet leaching carbon residues from retired lithium-ion batteries produced by the waste battery recycling industry. Among them, waste cathode carbon blocks and wet leaching carbon residues from retired lithium-ion batteries have a high soluble fluorine content and are classified as high-fluorine materials. Coal gangue and pyrolysis residues from oily sludge have rich aluminum, silicon and calcium contents, have a good solidification effect on soluble fluorine, and are classified as solidified materials.

[0016] As a preferred embodiment of the method for synergistic detoxification and full-component resource utilization of multi-source carbon-containing solid waste described in the present invention, the high-fluorine material includes at least one of carbon slag from wet leaching of retired lithium-ion batteries and waste cathodes from aluminum electrolysis, and the solidified material includes at least one of carbon slag from pyrolysis of oily sludge and coal gangue.

[0017] As a preferred embodiment of the method for synergistic detoxification and full-component resource utilization of multi-source carbon-containing solid waste described in the present invention, wherein: in the step S1, the particle size range of the high-fluorine material and the solidified material is the same, and the particle size range is one of 3-5 mm, 1-3 mm, 0.15-1 mm, 0.074-0.15 mm, and <0.074 mm.

[0018] As a preferred embodiment of the method for synergistic detoxification and full-component resource utilization of multi-source carbonaceous solid waste described herein, in step S2, the mass ratio of the high-fluorine material to the solidified material is 0.5:1 to 10:1, and the activation mixing time is 10 to 120 minutes. The high-fluorine material and the solidified material are mixed by mechanical activation to simultaneously enhance the reactivity of both.

[0019] As a preferred embodiment of the method for the synergistic detoxification and full-component resource utilization of multi-source carbon-containing solid waste described in the present invention, in step S3, the co-treatment temperature is 400-1000°C, and the co-treatment time is 0.5-5 hours. During the co-treatment process, the appropriate reaction temperature allows the soluble fluorine in the high-fluorine material to undergo a solidification reaction with the aluminum silicon calcium in the solidified material. Simultaneously, the combustion of carbon can promote the process and can generate calorific value as fuel, achieving resource utilization.

[0020] As a preferred embodiment of the method for synergistic detoxification and full-component resource utilization of multi-source carbon-containing solid waste described in the present invention, in which: in step S4, the inducer is one or more of aluminum hydroxide, sodium bifluoride, sodium metaaluminate, aluminum fluoride, and aluminum oxide, the amount of the inducer added is 1wt%-10wt%, and the pH control range is 4-8.

[0021] As a preferred embodiment of the method for synergistic detoxification and full-component resource utilization of multi-source carbon-containing solid waste described in the present invention, in step S4, the filtrate is refluxed into the aqueous solution of step S4.

[0022] As a preferred embodiment of the method for synergistic detoxification and full-component resource utilization of multi-source carbon-containing solid waste described in the present invention, in step S4, the molecular ratio of the cryolite is 2.8 to 3.0.

[0023] As a preferred embodiment of the method for synergistic detoxification and full-component resource utilization of multi-source carbon-containing solid waste described in the present invention, wherein: in the step S5, the tailings and the aluminosilicate solid waste are mixed in a mass ratio of 1:99-20:80, and the amount of the alkaline activator added is 5% to 20% of the total mass of the tailings and the aluminosilicate solid waste, and the alkaline activator is one of quicklime and slaked lime.

[0024] As a preferred embodiment of the method for synergistic detoxification and full-component resource utilization of multi-source carbon-containing solid waste described in the present invention, in which: in step S5, the aluminosilicate solid waste is one or more of lead-zinc slag, electrolytic manganese slag, slag, fly ash, silicon slag, and gold slag.

[0025] The beneficial effects of the present invention are as follows:

[0026] Starting from the resource and environmental interactive properties of multi-source carbon-containing solid waste, the present invention realizes the coordinated detoxification and resource utilization of all components of multi-source carbon-containing solid waste. The entire coordinated disposal process is a closed-loop treatment with no secondary pollution risk. At the same time, no additional chemical agents are required, and the disposal cost is low. The carbon component, fluoride component and other inorganic salt components in the multi-source carbon-containing solid waste can be respectively used for fuel, high-value cryolite products and high-performance cementitious materials, with significant economic and environmental benefits. DETAILED DESCRIPTION

[0027] The following will be a clear and complete description of the technical solutions in the embodiments. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.

[0028] According to one aspect of the present invention, the present invention provides the following technical solutions:

[0029] A method for collaborative detoxification and resource utilization of multi-source carbon-containing solid wastes, comprising the following steps:

[0030] S1. Control the particle size and dry the carbon-containing solid waste from multiple sources in sequence to separate it into high-fluorine materials and solidified materials;

[0031] S2. Add the high-fluorine material and the solidified material in proportion and activate them mechanically to obtain a mixed material;

[0032] S3, co-processing the mixed material at high temperature in an air environment to obtain tailings and fluorine-containing flue gas;

[0033] S4, passing the fluorine-containing flue gas into an aqueous solution for collection, and sequentially performing the steps of adding an inducer, adjusting the pH, and performing solid-liquid separation to obtain cryolite and a filtrate;

[0034] S5. Mix the tailings and aluminosilicate solid waste, add an alkali activator, and sequentially perform wet mixing, alkali activation, gasification, curing, and autoclaving to obtain a cementitious material.

[0035] On the one hand, the present invention makes full use of the environmental interaction properties of multi-source carbon-containing solid waste to achieve the synergistic detoxification of various toxic substances (soluble fluoride, highly toxic cyanide, organic matter, heavy metals). First, by utilizing the abundant calcium, aluminum, silicon, iron, and sulfur components in the solidified materials (pyrolysis carbon slag of oily sludge, coal gangue), relying on the combustion of carbonaceous materials to form a high-heat environment, the soluble fluoride with high leaching concentration in high-fluorine materials (wet leaching carbon slag of retired lithium-ion batteries, waste cathodes of aluminum electrolysis) is efficiently solidified, and the solidification rate of soluble fluoride is ≥99.4%. Secondly, by designing a high-temperature oxidation environment and using the high-heat environment generated by the combustion of carbonaceous materials, the oxidative decomposition of cyanide and organic matter in high-fluorine materials can be achieved, and the decomposition rate of cyanide and organic matter is ≥95.0%. Secondly, heavy metal elements (Ni, Zn, and Pb) in carbonaceous solid waste are simultaneously solidified by the aluminosilicate system in the solidified material during the soluble fluorine solidification process, with leaching concentrations of ≤0.01mg / L, 0.02mg / L, and 0.001mg / L, respectively. Finally, the innovative use of tailings to prepare cementitious materials allows the residual soluble fluorides to be deeply solidified through the synergistic effect of the quicklime calcification and the cementitious system, with leaching concentrations of ≤5mg / L.

[0036] On the other hand, the present invention makes full use of the resource interaction properties of multi-source carbon-containing solid waste to realize the resource utilization of all components of carbon-containing solid waste (carbon component, fluoride component, other inorganic salt components). First, low-sulfur carbon-containing solid waste (wet leaching carbon slag of retired lithium-ion batteries, waste cathodes of aluminum electrolysis) and high-sulfur carbon-containing solid waste (pyrolysis carbon slag of oily sludge and coal gangue) are co-processed to achieve the dilution of sulfur content (≤2%) while ensuring the calorific value, effectively improving the application potential and product value of multi-source carbon-containing hazardous waste in the power industry and cement industry. Secondly, high-ignition-point carbon-containing solid waste (wet leaching carbon slag of retired lithium-ion batteries, waste cathodes of aluminum electrolysis) and low-ignition-point carbon-containing solid waste (pyrolysis carbon slag of oily sludge and coal gangue) are co-processed, which can effectively slow down the combustion process and improve the combustion performance of multi-source carbon-containing hazardous waste. Thirdly, through the innovative design of the synergistic effect of the inducer and pH, high-value cryolite with a high molecular weight ratio (2.8-3.0) and qualified elemental composition (F ≥ 52%, Al ≥ 52%, Na ≤ 33%) was synthesized from fluorine-containing flue gas, successfully achieving high-value utilization of fluoride components. Finally, based on the high reactivity of the silicon and aluminum components in the tailings after high-temperature treatment, a cementitious material with excellent mechanical properties (compressive resistance ≥ 4.0 MPa) was prepared by low-dosage blending, realizing the resource utilization of multiple valuable components (aluminum, silicon, calcium, iron) in multi-source carbon-containing solid waste.

[0037] Preferably, the high-fluorine material includes at least one of wet leaching carbon slag from retired lithium-ion batteries and waste cathodes from aluminum electrolysis, and the solidified material includes at least one of pyrolysis carbon slag from oily sludge and coal gangue.

[0038] Preferably, in step S1, the particle size range of the high-fluorine material and the solidified material is the same, and the particle size range is one of 3-5 mm, 1-3 mm, 0.15-1 mm, 0.074-0.15 mm, and <0.074 mm.

[0039] Preferably, in step S2, the mass ratio of the high-fluorine material to the curing material is 0.5:1 to 10:1, and the activation mixing time is 10 to 120 minutes.

[0040] Preferably, in step S3, the co-treatment temperature is 400-1000° C., and the co-treatment time is 0.5-5 h.

[0041] Preferably, in step S4, the inducer is one or more of aluminum hydroxide, sodium bifluoride, sodium metaaluminate, aluminum fluoride, and aluminum oxide, the amount of the inducer added is 1wt%-10wt%, and the pH control range is 4-8.

[0042] Preferably, in step S4, the filtrate is refluxed into the aqueous solution of step S4. The concentrations of Na, Al, and F in the filtrate are measured before reflux, and based on this, the addition of the inducer is appropriately reduced to keep the ion concentration of the solution in step S4 close to the theoretical concentration.

[0043] Preferably, in step S4, the molecular ratio of the cryolite is 2.8 to 3.0.

[0044] Preferably, in step S5, the tailings and the aluminosilicate solid waste are mixed in a mass ratio of 1:99-20:80, and the amount of the alkaline activator added is 5% to 20% of the total amount of the tailings and the aluminosilicate solid waste.

[0045] Preferably, in step S5, the aluminosilicate solid waste is one or more of lead-zinc slag, electrolytic manganese slag, slag, fly ash, silicon slag, and gold slag.

[0046] The technical solution of the present invention is further described below with reference to specific embodiments.

[0047] In the following examples, the specific composition percentages by mass of the multi-source carbon-containing solid waste used are as follows:

[0048] Aluminum electrolysis waste cathode: 58.41% C, 19.63% F, 12.07% Na, 3.02% Al, 1.48% Ca, 0.83% Si, and the remainder impurities.

[0049] Carbon residue from pyrolysis of oily sludge: 34.86% C, 23.35% Fe, 1.05% Na, 3.82% Al, 5.15% Ca, 4.29% Si, and the remainder is impurities.

[0050] Carbon residue from wet leaching of retired lithium-ion batteries: 85.00% C, 3.92% Al, 0.80% Si, 0.39% P, and the remainder impurities.

[0051] Coal gangue: 25.66% C, 5.06% Fe, 1.15% Ca, 11% Al, 16.73% Si, 0.77% Na, and the remainder are impurities.

[0052] Example 1

[0053] A method for collaborative detoxification and resource utilization of multi-source carbon-containing solid wastes, comprising the following steps:

[0054] S1. Controlling the particle size and drying the waste cathode from aluminum electrolysis and the carbon residue from pyrolysis of oily sludge in sequence to obtain a high-fluorine material and a solidified material with a particle size range of 0.15-0.074 mm;

[0055] S2. The high-fluorine material and the solidified material were mixed in a planetary ball mill at a mass ratio of 3:7, with a mixing time of 30 min and a mixing speed of 250 r / min to obtain a mixed material;

[0056] S3. The mixed material is placed in a corundum ark and loaded into a muffle furnace, and then co-treated in an air environment at a co-treatment temperature of 800°C for a co-treatment time of 1.5 hours to obtain tailings and fluorine-containing flue gas. The solidification rate of soluble fluoride is 99.46%, and the decomposition rate of cyanide is 99.34% (the soluble fluorine and soluble cyanide contents of the waste cathode are measured before treatment. After adding oily sludge pyrolysis carbon residue for high-temperature treatment, the soluble fluorine and soluble cyanide contents of the treatment residue are measured and calculated based on the changes before and after treatment);

[0057] S4. The fluorine-containing flue gas is passed through an aqueous solution for collection. Inducer addition, pH control, and solid-liquid separation are sequentially performed to obtain cryolite product and filtrate. The filtrate is recycled for flue gas collection. The inducers are aluminum fluoride and aluminum hydroxide, added in an amount of 4wt%, and the pH control range is 6.

[0058] S5. The tailings and lead-zinc slag are mixed in a mass ratio of 5:95, and then an additional 15% of an alkali activator is added. The mixture is sequentially treated by wet mixing, alkali activation, gasification, curing, and autoclaving to obtain a cementitious material.

[0059] In this embodiment, the molecular ratio of the synthetic cryolite is 2.86, and the mass percentages of F, Al, and Na elements are 54.16%, 12.88%, and 31.37%, respectively; the compressive strength of the cementitious material is 5.5 MPa, and the soluble fluoride concentration is 2.47 mg / L.

[0060] Example 2

[0061] A method for collaborative detoxification and resource utilization of multi-source carbon-containing solid wastes, comprising the following steps:

[0062] S1. Sequentially perform particle size control and drying on carbon slag and coal gangue extracted by wet leaching of retired lithium-ion batteries to obtain a high-fluorine material and a solidified material with a particle size range of <0.074 mm;

[0063] S2. The high-fluorine material and the solidified material were mixed in a vibration ball mill at a mass ratio of 4:6, with a mixing time of 60 min and a mixing speed of 200 r / min to obtain a mixed material;

[0064] S3. The mixed material was placed in a corundum ark and loaded into a muffle furnace. The mixture was then co-treated in an air environment at a co-treatment temperature of 800°C for 2 hours to obtain tailings and fluorine-containing flue gas. The solidification rate of soluble fluoride was 99.76%, and the decomposition rate of organic matter was 95.81%.

[0065] S4. The fluorine-containing flue gas is passed through an aqueous solution for collection. Inducer addition, pH control, and solid-liquid separation are sequentially performed to obtain cryolite product and filtrate. The filtrate is recycled for flue gas collection. The inducer is sodium metaaluminate and aluminum hydroxide, the addition amount is 3%, and the pH control range is 6.

[0066] S5. The tailings and lead-zinc slag are mixed in a mass ratio of 7:93, and then an additional 15% of an alkali activator is added. The mixture is sequentially treated by wet mixing, alkali activation, gasification, curing, and autoclaving to obtain a cementitious material.

[0067] In this embodiment, the molecular ratio of the synthetic cryolite is 2.84, and the mass percentages of F, Al, and Na elements are 54.56%, 12.85%, and 31.08%, respectively; the compressive strength of the cementitious material is 4.2 MPa, and the soluble fluoride concentration is 1.08 mg / L.

[0068] Example 3

[0069] A method for collaborative detoxification and resource utilization of multi-source carbon-containing solid wastes, comprising the following steps:

[0070] S1. Sequentially perform particle size control and drying on carbon residue from wet leaching of retired lithium-ion batteries, carbon residue from pyrolysis of oily sludge, and coal gangue to obtain high-fluorine materials and solidified materials with a particle size range of <0.074 mm;

[0071] S2. Mix the high-fluorine material and the solidified material in a planetary ball mill at a mass ratio of 2:8 for 15 minutes at a mixing speed of 300 r / min to obtain a mixed material. The mass ratio of the oily sludge pyrolysis carbon residue to the coal gangue in the solidified material is 1:1.

[0072] S3. Place the mixed material in a corundum ark and load it into a muffle furnace. Then, co-treat it in an air environment at a co-treating temperature of 700°C for 1 hour to obtain tailings and fluorine-containing flue gas. The solidification rate of soluble fluoride is 99.54%, and the decomposition rate of organic matter is 99.04%.

[0073] S4. The fluorine-containing flue gas is passed through an aqueous solution for collection, and the induction agent is added, the pH is controlled, and the solid-liquid separation is performed in sequence to obtain a cryolite product and a filtrate. The filtrate is recycled to collect the flue gas. The induction agents are aluminum hydroxide and aluminum fluoride, the addition amount is 5wt%, and the pH control range is 5.5;

[0074] S5. The tailings and lead-zinc slag are mixed in a mass ratio of 3:97, and then an additional 15% of an alkali activator is added. The mixture is sequentially treated by wet mixing, alkali activation, gasification, curing, and autoclaving to obtain a cementitious material.

[0075] In this embodiment, the molecular ratio of the synthetic cryolite is 2.87, and the mass percentages of F, Al, and Na elements are 54.38%, 12.78%, and 31.28%, respectively; the compressive strength of the cementitious material is 5.1 MPa, and the soluble fluoride concentration is 1.14 mg / L.

[0076] Example 4

[0077] A method for collaborative detoxification and resource utilization of multi-source carbon-containing solid wastes, comprising the following steps:

[0078] S1. Controlling the particle size and drying the waste cathode from aluminum electrolysis, carbon residue from pyrolysis of oily sludge, and coal gangue in sequence to obtain high-fluorine materials and solidified materials with a particle size range of 0.15-0.074 mm;

[0079] S2. Mix the high-fluorine material and the solidified material in a planetary ball mill at a mass ratio of 3:7 for 15 minutes at a mixing speed of 300 r / min to obtain a mixed material. The mass ratio of the oily sludge pyrolysis carbon residue to the coal gangue in the solidified material is 2.5:1.

[0080] S3. Place the mixed material in a corundum ark and load it into a muffle furnace. Then, co-treat it in an air environment at a co-treating temperature of 900°C for 3 hours to obtain tailings and fluorine-containing flue gas. The solidification rate of soluble fluoride is 99.98%, and the decomposition rate of cyanide is 98.16%.

[0081] S4. The fluorine-containing flue gas is passed through an aqueous solution for collection, and the induction agent is added, the pH is controlled, and the solid-liquid separation is performed in sequence to obtain a cryolite product and a filtrate. The filtrate is recycled to collect the flue gas. The induction agents are aluminum hydroxide and aluminum fluoride, the addition amount is 6wt%, and the pH control range is 5;

[0082] S5. The tailings and lead-zinc slag are mixed in a mass ratio of 10:90, and then an additional 15% of an alkali activator is added. The mixture is sequentially treated by wet mixing, alkali activation, gasification, curing, and autoclaving to obtain a cementitious material.

[0083] In this embodiment, the molecular ratio of the synthetic cryolite is 2.84, and the mass percentages of F, Al, and Na elements are 54.27%, 12.92%, and 31.24%, respectively; the compressive strength of the cementitious material is 4.2 MPa, and the soluble fluoride concentration is 0.12 mg / L.

[0084] Comparative Example 1

[0085] S1. Controlling the particle size and drying the waste cathode from aluminum electrolysis and the carbon residue from pyrolysis of oily sludge in sequence to obtain a high-fluorine material and a solidified material with a particle size range of 0.15-0.074 mm;

[0086] S2. Mixing the high-fluorine material and the solidified material in an agate mortar at a mass ratio of 3:7 to obtain a mixed material;

[0087] S3. The mixed material was placed in a corundum ark and loaded into a muffle furnace. The mixture was then co-treated in an air environment at a co-treatment temperature of 800°C for 1.5 hours to obtain tailings and fluorine-containing flue gas. The solidification rate of soluble fluoride was 97.68%, and the decomposition rate of cyanide was 98.12%.

[0088] S4. The fluorine-containing flue gas is passed through an aqueous solution for collection. Inducer addition, pH control, and solid-liquid separation are sequentially performed to obtain cryolite product and filtrate. The filtrate is recycled to collect the flue gas. The inducer is aluminum fluoride and aluminum hydroxide, the addition amount is 4%, and the pH control range is 6.

[0089] S5. The tailings and lead-zinc slag are mixed in a mass ratio of 5:95, and then an additional 15% of an alkali activator is added. The mixture is sequentially treated by wet mixing, alkali activation, gasification, curing, and autoclaving to obtain a cementitious material.

[0090] In this comparative example, the molecular ratio of the synthetic cryolite is 2.61, and the mass percentages of F, Al, and Na elements are 57.14%, 12.88%, and 28.66%, respectively; the compressive strength of the cementitious material is 3.2 MPa, and the soluble fluoride concentration is 76.47 mg / L.

[0091] In Comparative Example 1, the mixing method of the high-fluorine material and the solidified material in step S2 was changed from mechanical mixing to grinding mixing compared with the embodiment, and the mixing uniformity decreased, resulting in the reaction activity not being effectively improved. The solidification rate of the soluble fluoride and the decomposition rate of the cyanide in step S3 were both reduced, resulting in an increase in the F content in the subsequent steps, a decrease in the cryolite molecular ratio, a decrease in the compressive strength of the gel material, an increase in the leaching concentration of the soluble fluoride, and the failure to fully utilize the components in the multi-source carbonaceous solid waste.

[0092] Comparative Example 2

[0093] 1. The particle size of the waste cathode from aluminum electrolysis and the carbon residue from pyrolysis of oily sludge are controlled and dried in sequence to obtain high-fluorine materials and solidified materials with a particle size range of 0.15-0.074 mm;

[0094] S2. The high-fluorine material and the solidified material were mixed in a planetary ball mill at a mass ratio of 3:7 for 30 min at a mixing speed of 250 r / min to obtain a mixed material;

[0095] S3. The mixed material was placed in a corundum ark and loaded into a muffle furnace. The mixed material was then co-treated under a nitrogen atmosphere at a co-treatment temperature of 800°C for 1.5 hours to obtain tailings and fluorine-containing flue gas. The solidification rate of soluble fluoride was 97.16%, and the decomposition rate of cyanide was 98.04%.

[0096] S4. The fluorine-containing flue gas is passed through an aqueous solution for collection. Inducer addition, pH control, and solid-liquid separation are sequentially performed to obtain cryolite product and filtrate. The filtrate is recycled to collect the flue gas. The inducer is aluminum fluoride and aluminum hydroxide, the addition amount is 4%, and the pH control range is 6.

[0097] S5. The tailings and lead-zinc slag are mixed in a mass ratio of 5:95, and then an additional 15% of an alkali activator is added. The mixture is sequentially treated by wet mixing, alkali activation, gasification, curing, and autoclaving to obtain a cementitious material.

[0098] In this comparative example, the molecular ratio of the synthetic cryolite is 2.59, and the mass percentages of F, Al, and Na elements are 57.01%, 12.92%, and 28.48%, respectively; the compressive strength of the cementitious material is 3.0 MPa, and the soluble fluoride concentration is 54.78 mg / L.

[0099] In Comparative Example 2, the co-processing atmosphere in step S3 was changed from air atmosphere to nitrogen atmosphere compared with that in the embodiment, resulting in the inability of the carbon material to burn, which was insufficient to provide sufficient heat to promote the solidification of fluoride and the decomposition of cyanide. The solidification rate of soluble fluoride and the decomposition rate of cyanide in step S3 both decreased, resulting in an increase in the F content in subsequent steps, a decrease in the cryolite molecular ratio, a decrease in the compressive strength of the gel material, an increase in the leaching concentration of soluble fluoride, and insufficient utilization of the components in the multi-source carbonaceous solid waste.

[0100] It can be seen from the above embodiments and comparative examples that the present invention, starting from the resource and environmental interactive properties of multi-source carbon-containing solid waste, realizes the coordinated detoxification and resource utilization of all components of multi-source carbon-containing solid waste. The entire coordinated disposal process is a closed-loop treatment without the risk of secondary pollution. At the same time, no additional chemical agents are required, and the disposal cost is low. The carbon component, fluoride component and other inorganic salt components in the multi-source carbon-containing solid waste can be respectively used for fuel, high-value cryolite products and high-performance cementitious materials, and have significant economic and environmental benefits.

[0101] The above description is only a preferred embodiment of the present invention and does not limit the patent scope of the present invention. All equivalent structural transformations made by using the contents of the present invention specification under the inventive concept of the present invention, or direct / indirect application in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A method for synergistic detoxification and resource utilization of all components of multi-source carbon-containing solid waste, characterized in that: The steps include: S1. Control the particle size and dry the carbon-containing solid waste from multiple sources in sequence to divide them into high-fluorine materials and solidified materials; S2, adding the high-fluorine material and the solidified material in proportion and activating and mechanically mixing them to obtain a mixed material; S3, placing the mixed material in a high temperature treatment device for co-treatment in an air environment to obtain tailings and fluorine-containing flue gas; S4, passing the fluorine-containing flue gas into an aqueous solution for collection, and sequentially performing the steps of adding an inducer, adjusting the pH value, and separating the solid from the liquid to obtain cryolite and a filtrate; S5. Mix the tailings and aluminosilicate solid waste, add an alkali activator, and sequentially perform wet mixing, alkali activation, gasification, curing and autoclaving to obtain a cementitious material.

2. The method for collaborative detoxification and full-component resource utilization of multi-source carbon-containing solid waste according to claim 1, characterized in that: In the step S1, the high-fluorine material includes at least one of carbon slag from wet leaching of retired lithium-ion batteries and waste cathodes from aluminum electrolysis, and the solidified material includes at least one of carbon slag from pyrolysis of oily sludge and coal gangue.

3. The method for collaborative detoxification and full-component resource utilization of multi-source carbon-containing solid waste according to claim 2, characterized in that: In the step S1, the particle size range of the high-fluorine material and the solidified material is the same, and the particle size range is one of 3-5 mm, 1-3 mm, 0.15-1 mm, 0.074-0.15 mm, and <0.074 mm.

4. The method for collaborative detoxification and full-component resource utilization of multi-source carbon-containing solid waste according to claim 1, characterized in that: In the step S2, the mass ratio of the high-fluorine material to the solidified material is 0.5:1 to 10:1, and the activation mixing time is 10 to 120 minutes.

5. The method for collaborative detoxification and full-component resource utilization of multi-source carbon-containing solid waste according to claim 1, characterized in that: In step S3, the co-treatment temperature is 400-1000° C., and the co-treatment time is 0.5-5 h.

6. The method for collaborative detoxification and full-component resource utilization of multi-source carbon-containing solid waste according to claim 1, characterized in that: In step S4, the inducer is one or more of aluminum hydroxide, sodium bifluoride, sodium aluminate, aluminum fluoride, and aluminum oxide, the amount of the inducer added is 1wt%-10wt%, and the pH control range is 4-8.

7. The method for collaborative detoxification and full-component resource utilization of multi-source carbon-containing solid waste according to claim 1, characterized in that: In the step S4, the filtrate is refluxed into the aqueous solution in step S4.

8. The method for collaborative detoxification and full-component resource utilization of multi-source carbon-containing solid waste according to claim 1, characterized in that: In the step S4, the molecular ratio of the cryolite is 2.8 to 3.

0.

9. The method for collaborative detoxification and full-component resource utilization of multi-source carbon-containing solid waste according to claim 1, characterized in that: In the step S5, the tailings and the aluminosilicate solid waste are mixed in a mass ratio of 1:99-20:80, and the amount of the alkaline activator added is 5% to 20% of the total mass of the tailings and the aluminosilicate solid waste. The alkaline activator is one of quicklime and slaked lime.

10. The method for collaborative detoxification and full-component resource utilization of multi-source carbon-containing solid waste according to claim 9, characterized in that: In step S5, the aluminosilicate solid waste is one or more of lead-zinc slag, electrolytic manganese slag, slag, fly ash, silicon slag, and gold slag.

Citation Information

Patent Citations

  • High-temperature continuous treatment method for treating electrolytic aluminum waste cathodes

    CN106269787A

  • Method for synergistically recycling aluminum electrolysis overhaul slag and mining and metallurgy waste slag

    CN114888036A

  • Synergistic recycling method for aluminum electrolysis carbon-containing hazardous waste

    CN116274310A

  • Method and apparatus for treating fluorine-containing waste

    JP2013087267A